Designing an English Syllabus for Architecture Students: Matching Students’ English Skills and Future Jobs - Murtiningsih, Tenny; Amelia, Rizky (SALEE: Study of Applied Linguistics and English Education, 2023)
Designing an English Syllabus for architecture students is important to match what they are studying at the university and their future job later. Through the syllabus, lecturers are aware of the mapping between learning outcomes, materials, teaching methods, and assessment and most importantly what students need in the future. English instruction for architecture students is included as English for Specific Purposes. In this circumstance, the lecturers must provide students with the students needs in their field, as outlined in the syllabus. To meet these requirements, the researchers conducted a Research and Development to develop an English Syllabus for Architecture students adapted from Borg and Gall (2003) including (1) needs analysis, (2) writing the product, (3) validating the product, (4) revising the product and (5) final product. Meanwhile, Language Program Development (LPD) by Yalden (1987) is chosen as the model of syllabus development. Thirty three architecture students, three architecture lecturers, and three architecture professional workers as alumni and stakeholder were involved. They were given a questionnaire, an interview, and a validation sheet to collect and triangulate the data. Then, the syllabus was developed, validated, and revised. The results showed that the syllabus of English for Architecture Students has been developed as an integrated syllabus, and it is feasible to use.